Sistema de presentación de video juegos a través de hologramas reales y tecnología de software. - Cola Pérez, Cristian Andrés (2017)
The inefficiency in the advertising processes of video game products in the VirtualNet store located in the province of Cotopaxi, canton Latacunga, La Merced street, Guayaquil and Toledo, has been a problem reflected throughout its commercial life, therefore in the present work proposes to develop a system of presentation of video game products in the form of a hologram which will be in the shop described above. In order to solve the problem, the SCRUM software development methodology was implemented. It consists of 5 phases, which are: Planning, Estimation, Implementation, Review and Launch, which allow good use for the life cycle of the product; obtaining as a result a system that meets all the needs that were established during the taking of requirements, reflecting a vanguard system in the advertising of the products of the store in a holographic way.